Protein hydrolysates from Italian sea bream and sea bass aquaculture side streams – chemical, biological, and techno-functional characterization - Jenssen, Marte; Matic, Josipa; Sone, Izumi; Solberg, Nina Therese; Wubshet, Sileshi; Lian, Kjersti (Frontiers in Marine Science, 2025)
With the increasing demand for food and sustainable food processes, using side streams from food production has gained increased attention. After fish filleting, a significant amount of the biomass, such as heads, viscera, backbones, and skins, is left unused or utilized for low-value purposes. This biomass has high contents of valuable proteins and lipids that can be used for higher-value products, such as for human consumption or feed. This study used residual biomass from Italian sea bream and sea bass aquaculture to produce protein hydrolysates. Before hydrolysis, the biomass was pre-processed using an industrial patented dehydration process. Both pre-processed and un-processed biomasses were hydrolyzed, testing four different commercial proteases. The proximate composition of the starting materials was assessed. After hydrolysis, the yield, proximate composition, total amino acid content, and peptide size distribution of the hydrolysates were determined, showing high protein contents above 87% for all hydrolysates. The oil samples obtained after hydrolysis were analyzed for oxidation products. The protein hydrolysates were analyzed for different biological activities including antioxidant activity, anti-diabetes activity, and effect on cell growth and glucose uptake. In addition, the emulsifying properties of the hydrolysates were evaluated. The results indicate variations in chemical composition and biological activity between the hydrolysates. The most prominent differences were yield (on a dry matter basis), which was higher for the hydrolysates produced from un-processed biomass, and molecular weight distribution, which showed that the hydrolysates produced from pre-processed biomass were less hydrolyzed (AMW above 3000 g/mol) compared to hydrolysates from un-processed biomass (AMW below 2600 g/mol). In addition, the antioxidant activity was higher for the hydrolysates from un-processed biomass (22-25 µM TEAC) compared to the hydrolysates from pre-processed biomass (around 15 µM TEAC), assayed at 100 µg/mL. The results of this study are highly relevant for further evaluation and development of pre-processing technology and its effect on the final protein hydrolysate products.